Multiplier agents of blood and bone marrow donation capture: extension project experience (Research, Society and Development, 2022)
This is an experience report of the University Extension Project "Training of Multiplier Agents in the Capture of Blood Donation and Bone Marrow", in partnership with the Homocentric of the State of Alagoas, in which the activities were carried out in 2019. With the goal of presenting the selection process, training, actions taken in the capture of blood and bone marrow donors, which encourages the internal and external community of the university about the importance of the act, through strategies of welcome, support and information about the whole donation process. It aims to contribute to the dissemination of information, helping to demystify myths, raising awareness, and the citizens' adherence to the social causes in question, allowing the growth of the blood stock and the maintenance of the services offered. It is hoped that this work can sensitize the community of readers to develop new studies, besides stimulating the development of projects associated with this theme, disseminating information and necessary changes for effective adherence and commitment aiming at blood and bone marrow donation. The project provided an opportunity for the students to have contact with the employees of the Blood Center, favoring a better academic education through a more articulated professional practice, by sharing competencies and skills with future health professionals.